Level of systemic inflammation markers and clinical course in patients with stable ischemic heart disease with and without coronary atherosclerosis - V.I. Tseluyko; T.V. Pylova (Кардіохірургія та інтервенційна кардіологія)
The aim – to investigate the relation between levels of inflammatory factors and clinical course of the ischemic heart disease with and without coronary atherosclerosis.